Photodetectors Based on Lead Sulfide Quantum Dot and Organic Absorbers for Multispectral Sensing in the Visible to Short‐Wave Infrared Range. (13th April 2022) - Pejović, Vladimir; Georgitzikis, Epimitheas; Lieberman, Itai; Malinowski, Paweł E.; Heremans, Paul; Cheyns, David
Abstract: Multispectral imaging in short‐wave infrared (SWIR) is a powerful analytical technique because of the distinctive spectral properties of many materials in this range. However, conventional SWIR image sensors are beyond the reach of many applications due to their high price. Image sensors based on colloidal quantum dots (CQDs) are expected to deliver affordable infrared image sensors to wider application scope. So far, the demonstrated CQD image sensors do not have a multispectral capability. Here, a dual‐band photodetector based on PbS CQDs is presented. By engineering the surface of CQDs, two oppositely facing pn junctions are fabricated in series, which enable sensing in two spectral channels. Furthermore, an optical cavity is designed that reduces the spectral crosstalk between the two channels and simultaneously enables wavelength‐tunability in one channel. Finally, an organic photodiode (OPD) is integrated with a PbS CQD photodiode in a single device, leveraging a high sensitivity in visible and near‐infrared (NIR) characteristics for OPDs. The presented photodetectors exhibit low dark current below 500 nA cm −2 at 1 V bias, a fast response measured in microseconds, as well as high external quantum efficiency, reaching 70% in NIR and 30% in SWIR. Abstract : Thin‐film semiconductors offer attractive opportunities for achieving optoelectronic functionalities that are not easily accessible with conventional bulk semiconductors. This paper presents a tunable dual‐band photodetector for multispectral sensing in the visible to short‐wave infrared range. Organic and inorganic colloidal quantum dot absorbers are integrated into a single vertically stacked structure to leverage the best features of both material systems.